2014
DOI: 10.3390/ani4040583
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Relative Humidity Inside Trailers During Finishing Pig Loading and Transport in Cold and Mild Weather

Abstract: Simple SummaryThe multi-site nature of the modern pork industry makes transport an essential part of swine production. It is well documented that transport induces stress in pigs. Bedding levels can have a significant effect on temperature and relative humidity inside the trailer. This study aims to determine the effects of bedding level on trailer temperature and humidity between average air temperatures of 4 °C and 18 °C. Relative humidity was greatest when higher levels of bedding were used during loading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
(9 reference statements)
0
5
2
3
Order By: Relevance
“…Also, pigs transported on the second floor of the truck (mean = 40.1) showed a difference of 1.2 • C when compare pigs located on the first floor (mean = 38.9). [13] showed an increasing of dead pigs with increase the ST after transportation.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Also, pigs transported on the second floor of the truck (mean = 40.1) showed a difference of 1.2 • C when compare pigs located on the first floor (mean = 38.9). [13] showed an increasing of dead pigs with increase the ST after transportation.…”
Section: Resultsmentioning
confidence: 91%
“…In the present study, the schedule of pigs transportation during the afternoon is unsuitable for the animals (Table 2). The truck micro-environment is determined by AT, RH and WS [13]. However, other variables also affect the truck microenvironment during transportation, such as stocking density, size, weight and age of animals, and vehicle motion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration of trailer thermal environment under TQA guidelines is merited to better understand the factors contributing to undesirable conditions. Projects commissioned by the NPB to evaluate and revise TQA guidelines found that the guidelines required minimal changes [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. It was reported by [ 30 ] that the highest rate of DOD pigs at arrival occurred when low boarding (<30% coverage) was used for outside temperature < 5 °C.…”
Section: Introductionmentioning
confidence: 99%
“…O transporte engloba complexas operações que fazem com que os animais vivenciem diversas experiências estressoras MCGLONE et al, 2014b), tais como extremos de temperatura, vibração e alternâncias de aceleração, estímulos sonoros, confinamento e aglomeração , os quais representam uma nova experiência aos suínos, fator esse agravante para o estresse dos mesmos . Pode ocorrer em mais de um estágio do ciclo produtivo de suínos (FAUCITANO; GOUMON, 2018) e, juntamente com as etapas de carregamento e descarregamento, representa um importante evento de estresse na vida dos mesmos (MARCHANT-FORDE; MARCHANT-FORDE, 2008;SCHWARTZKOPF-GENSWEIN et al, 2012;MCGLONE et al, 2014;NEWMAN et al, 2014), influenciando também no índice de mortalidade (DALLA COSTA et al, 2019a).…”
Section: Transporteunclassified